1992
DOI: 10.1139/z92-212
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age and body weight on the proportion of females breeding in a population of roe deer (Capreolus capreolus)

Abstract: The reproductive state of female roe deer (Capreolus capreolus) (n = 140) caught during 4 consecutive winters (January and February) was determined from progesterone concentrations in blood samples. We found that (i) females older than 20 months were pregnant almost every year, indicating that though monoestrous, this species can achieve a very high conception rate (98%); (ii) a significant proportion of females 20 months of age (corresponding to the usual age at first pregnancy) had not reached sexual maturit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
134
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(145 citation statements)
references
References 23 publications
9
134
0
2
Order By: Relevance
“…In most populations of roe deer, it is generally found that nearly all females older than two years ovulate and produce fawns; however, in populations where body masses are lower (<20 kg, Gaillard et al, 1992), the age of the first reproduction can be prolonged to three or four years (Andersen et al 1998).…”
Section: Doe Body Mass(kg) /mentioning
confidence: 99%
“…In most populations of roe deer, it is generally found that nearly all females older than two years ovulate and produce fawns; however, in populations where body masses are lower (<20 kg, Gaillard et al, 1992), the age of the first reproduction can be prolonged to three or four years (Andersen et al 1998).…”
Section: Doe Body Mass(kg) /mentioning
confidence: 99%
“…However, in mammals, field data suggest that, following an initial period of relatively low productivity prior to adulthood, the number of offspring produced per female subsequently remains fairly constant, though in some cases there may be a slight decline during later life (Sadleir 1987, Mitchell and Brown 1974, Sinclair 1977, Guinness et al 1978. For roe deer Capreolus capreolus (Linnaeus, 1758) some authors have also suggested that female productivity declines during the later stages of life (Borg 1971, Kaluziriski 1982, although Gaillard et al (1992) found a uniformly high level of fecundity once does were more than two years of age. Few studies have been able to demonstrate whether age-related changes in productivity are adaptive, or merely the result of puberty and senescence, although Clutton-Brock (1984) suggests that there is evidence that red deer Cervus elaphus hinds, as they grow older, invest more heavily in their calves at lactation, ensuring increased rates of juvenile survival at the stage of terminal investment.…”
Section: Introductionmentioning
confidence: 99%
“…It is often stated that in female ungulates, after primiparity is reached, no further cost of low initial weight exists (Gaillard, Sempere et al, 1992;Langvatn et al, 1996), and that lifetime reproductive success is therefore closely related to longevity (Gaillard, Festa-Bianchet, Delorme et al, 2000), as there is little variation in reproduction between prime-aged females. Our results show, however, that domestic ewes with a high initial body weight reared larger lambs in subsequent years (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies report that body mass during prime age does not affect variation in reproduction notably (Langvatn et al, 1996;Gaillard, Festa-Bianchet, Delorme et al, 2000). For example, in a Norwegian population almost all red deer hinds > 3 years old ovulated (Langvatn et al, 1996), and in France 98% of all roe deer Capreolus capreolus does 2 years old or older were pregnant during winter (Gaillard, Sempere et al, 1992). The number of offspring raised by roe deer and bighorn sheep was not found to be related to female mass after the effect of longevity was accounted for (Gaillard, Festa-Bianchet, Delorme et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation